Management of the Properties of Shipbuilding Expanded Clay Lightweight Concrete - Kroviakov, Sergii; Mishutin, Andrii; V. Pishev, O (International Journal of Engineering and Technology, 2018)
The purpose of the research was to improve the strength and durability of shipbuilding expanded clay lightweight concrete by using modifiers, fibers and optimizing the composition of concrete. The four-factor experiment was carried out according to the optimal plan. The experiment varied, the amount of sulfate-resistant Portland cement, silica fume and polypropylene fiber. The content of expanded clay gravel in concrete also varied. Strength, watertighness, frost resistance and average density of ship-building expanded clay lightweight concrete of various compositions are investigated. The rational quantity of modifiers and fibers is determined. It is shown that shipbuilding expanded clay concrete has high watertighness and frost resistance, which ensures their durability when operating afloat. The use of lightweight concrete allows increasing the load carrying of floating structures and improving the working conditions of personnel. Normative documents for the production of concrete for floating reinforced concrete structures inUkrainehave been developed.Â